Microscopic modelling of motorway diverges - Wall, G. T.; Hounsell, N. B. (European Journal of Transport and Infrastructure Research, 2005)
This paper describes research looking at the design and operation of motorway diverges using the microscopic computer program SISTM. A diverge is the area of the motorway or other major road where drivers can leave the main carriageway. Low cost measures including the installation of alternative designs (such as the Ghost Island diverge) are assessed which could improve the operation, capacity and driving behaviour at the diverge. Following on from a recent study reviewing the diverging flow-region diagram (used in the UK as a tool to help traffic engineers select the most suitable diverge layout for a particular site with given downstream mainline and diverging flows), it was thought that microscopic models could offer potential benefits in confirming such a choice (particularly in border line situations) as driving behaviour aspects which affect capacity are not catered for in the diagram. SISTM has been used to evaluate existing and alternative diverge layouts in terms of their throughput as well as several other parameters. Modelled and observed data for the speed-flow relationship and the lane distribution of the mainline was compared and differences noted in order that the results could be interpreted correctly. A theoretical comparison of four layouts was carried out; Taper, Parallel, Taper lane drop and Ghost Island diverge. The link between throughput and lane distribution on the mainline before the diverge was also assessed as well as the importance of lane and exit choice. This research presents a summary of some of the key results from the modelling along with a discussion of their accuracy and application. Conclusions and recommendations are made with regard to design implications for diverges along with a list of modelling requirements (essential and desirable) for motorway diverges.